Effect of jet milling processing on microstructure and mechanical properties of the sintered tungsten powders - LI Xing-yu; ZHANG Lin; QIN Ming-li; WEI Zi-chen; QUE Zhong-you; QU Xuan-hui (Fenmo yejin jishu)
Commercial tungsten powders were modified by jet milling, the effects of jet milling treatment and particle size distribution on the microstructure and mechanical properties of the sintered tungsten body were studied. The results show that, the tungsten powders treated by jet milling in the narrower particle size distribution can achieve the better packing homogeneity, eliminate the irregular coarse pores formed during sintering, improve the sintering uniformity, and increase the relative density of the sintered body; the relative density of the sintered body increases from 90.7% to 92.8%, and the bending strength from 238.5 MPa to 292.4 MPa. The tungsten powders in the narrow particle size distribution with the good dispersibility can eliminate the irregular coarse pores in sintered body, which is the key factor to improve the mechanical properties of the sintered body.